2018
DOI: 10.3390/v10080391
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis and Characterization of the Complete Hepatitis E Virus Genome (Zoonotic Genotype 3) in Swine Samples from Mexico

Abstract: Hepatitis E virus (HEV) is an emerging public health problem with an estimated 20 million infections each year. In Mexico, Orthohepevirus A, genotype 2, has been reported in humans, but genotype 3 has only been reported in swine (zoonotic). No diagnostic tests are publicly available in Mexico, and only partial sequences have been reported from swine samples. Hence, research is necessary to determine circulating strains, understand the features and dynamics of infection on pig farms, determine how to implement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The finding of three genotypes in Mexico places the country as unique in Latin America, where HEV-Gt1 and -Gt3 have been found in humans and HEV-Gt3 in swine (Figure 2). swine was confirmed over the complete genome sequencing of one sample and two partial genomes [89]. In association with serological evaluation, these studies confirmed the endemicity of HEV in animals intended for human consumption, emphasizing the need for adequate food safety and surveillance systems.…”
Section: The Molecular Epidemiology Of Hev In Mexico: a Challenge To ...supporting
confidence: 53%
See 3 more Smart Citations
“…The finding of three genotypes in Mexico places the country as unique in Latin America, where HEV-Gt1 and -Gt3 have been found in humans and HEV-Gt3 in swine (Figure 2). swine was confirmed over the complete genome sequencing of one sample and two partial genomes [89]. In association with serological evaluation, these studies confirmed the endemicity of HEV in animals intended for human consumption, emphasizing the need for adequate food safety and surveillance systems.…”
Section: The Molecular Epidemiology Of Hev In Mexico: a Challenge To ...supporting
confidence: 53%
“…Molecular detection of HEV-RNA in clinical and epidemiological contexts pursues two main goals: diagnosis of active infections and genome sequencing for genotyping. In Mexico, only scientific studies have been published addressing molecular HEV detection, and for most Latin American countries, short partial sequences of the HEV genome are commonly reported (Supplementary Table S1) [25,[27][28][29]40,89,.…”
Section: The Molecular Epidemiology Of Hev In Mexico: a Challenge To ...mentioning
confidence: 99%
See 2 more Smart Citations